A baixa legitimação da informação contábil nos processos de licitação pública - Ribeiro, Rafael Borges (2020)
This research questions whether factors related to regulatory legitimacy are contributing so that stakeholders do not perceive accounting information as an instrument capable of evaluating the economic and financial capacity of companies. To achieve this objective, theoretical discussion, focus group, interviews and document analysis were used as methodological strategies, with the aim of understanding and analyzing the phenomenon from different perspectives. The results showed that in the context of public bids, accounting information, present in the economic and financial qualification stage (QEF), has not been seen as legitimate by information users. The economic and financial qualification stage has proved to be insufficient and unable to certify the company's economic and financial assessment, in order to comply with the contractual object. In general, stakeholders, in the bidding process, use accounting information only as a ceremonial rite. The thesis discusses the preponderance of the principle of Isonomy (wide competition) to the detriment of the principle of Advantage, in which the standard limits the requirement of useful information to the decision-making process in the economic and financial qualification stage. It was also verified the absence of necessary characteristics to the financial information to be useful, as recommended by the Basic Conceptual Framework (CPC-00). These findings demonstrate the low legitimacy of accounting information due to the fact that they differ conceptually from the accounting standards and resolutions of the Federal Accounting Council of Brazil, resulting in loss of relevance of accounting information. It has also been shown that when accounting information is not perceived as legitimate by the actors, the reduction of information asymmetry is impacted. In view of the above, it is suggested that the disclosure of financial statements of companies that claim to be recipientes of public resources is mandatory, that the economic and financial qualification stage is carried out by an accounting professional with the respective opinion and that there is an increase in the sharing of information by companies with federal entities. From a theoretical point of view, this research contributes by indicating that the low perceived legitimacy of accounting information is the factor that contributes to its ceremonial use. From a practical point of view, this research shows that a consistent analysis of the economic and financial qualification stage mitigates the problems of discontinuities in contracts of companies that do not have financial capacity and reduces public losses. This explanation could be used in other studies investigating the use of accounting information.